Structural, optical, and dielectric properties of Co2+: Zn2SiO4 glass-ceramics for blue phosphor used in optoelectronic devices - Siti Aisyah, Abdul Wahab; Khamirul Amin, Matori; Sidek, Hj Abd Aziz; Mohd Hafiz, Mohd Zaid; Mohd Mustafa, Awang Kechik; Idza Riati, Ibrahim; Mohammad Zulhasif, Ahmad Khiri; Nuraidayani, Effendy; Muhammad Najibudin, Abu Bakar (Elsevier Science, Ltd., 2022)
For the first time, the author reported the fabrication and characterizations of Co2+ doped Zn2SiO4 (Zn2SiO4: Co2+) using the recycled waste white rice husk ash (WRHA) based on empirical formula (Co3O4)1.0[(ZnO)55.0(WRHA)45.0]99.0 and produced by using melt-quenching technique. The precursor glass was heat treated at 700 ℃ until 950 ℃. The X-ray diffraction (XRD) result of Zn2SiO4: Co2+ showed that β- Zn2SiO4 started to form at 750 ℃ and single phase of α-Zn2SiO4 remain stable at 950 ℃. The Fourier transform infrared spectroscopy (FTIR) confirmed the formation of Zn2SiO4: Co2+ by showing eight significant vibrational bands. One triplet absorption band occurred at around 450 - 700 nm attributed to 4A2 → 4T1 (4P) optical transition of Co2+ ions that gives blue colour towards the Zn2SiO4: Co2+ sample. Emission spectroscopy of Zn2SiO4: Co2+ exhibit five different peaks corresponded to blue emission (~416nm, ~441 nm, ~461 nm and ~481 nm) and green emission (~527 nm) under excitation at 325 nm. Such luminescence properties making Zn2SiO4: Co2+ as a potential phosphor material especially in providing blue emission supported by the excellent dielectric properties.